Multicultural Approach in Islamic Religious Education to Strengthen Interfaith Harmony - Nisa, Hafidzotun; Hijriyah , Umi (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract Indonesia, as a country with cultural, ethnic and religious diversity, faces great challenges in maintaining harmony between religious communities. Islamic Religious Education (PAI) has a strategic role in instilling moral, ethical and religious values in the younger generation. However, amidst this diversity, it is important to develop an approach that can foster tolerance, mutual respect and harmony between religious communities. One approach that is relevant and effective is a multicultural approach in Islamic religious education. This research aims to explore how a multicultural approach in PAI can strengthen relations between religious communities and create a harmonious atmosphere in society. This approach not only teaches Islamic teachings in depth, but also opens up space for understanding the teachings of other religions, respecting differences, and encouraging dialogue between religions. Through a multicultural approach, it is hoped that students can understand the universal values contained in various religions, which in turn will strengthen the spirit of tolerance and togetherness. The method used in this research is a qualitative study with a phenomenological approach, involving observation, interviews and document analysis. The results of the research show that the application of a multicultural approach in PAI is able to increase mutual respect and cooperation between religious communities, as well as foster a sense of pride in their respective religious identities. Although there are challenges in implementation, such as resistance to curriculum changes and a lack of understanding of multicultural concepts, this approach has proven effective in creating a more inclusive and peaceful environment. This research contributes to the development of an Islamic religious education model that not only focuses on teaching religious teachings, but also on forming social character that strengthens harmony between religious communities. It is hoped that the results of this research can become a reference for educational policy makers to implement a multicultural approach in the Islamic religious education curriculum in Indonesia. Keywords: Islamic Religious Education, Multicultural Approach, Inter-Religious Harmony Abstrak Indonesia, sebagai negara dengan keragaman budaya, suku, dan agama, menghadapi tantangan besar dalam menjaga keharmonisan antar umat beragama. Pendidikan Agama Islam (PAI) memiliki peran strategis dalam menanamkan nilai-nilai moral, etika, dan keagamaan kepada generasi muda. Namun, di tengah keberagaman ini, penting untuk mengembangkan pendekatan yang dapat memupuk sikap toleransi, saling menghormati, dan kerukunan antar umat beragama. Salah satu pendekatan yang relevan dan efektif adalah pendekatan multikultural dalam pendidikan agama Islam. Penelitian ini bertujuan untuk mengeksplorasi bagaimana pendekatan multikultural dalam PAI dapat mempererat hubungan antar umat beragama dan menciptakan suasana yang harmonis di masyarakat. Pendekatan ini tidak hanya mengajarkan ajaran Islam secara mendalam, tetapi juga membuka ruang bagi pemahaman terhadap ajaran agama lain, menghargai perbedaan, dan mendorong dialog antar agama. Melalui pendekatan multikultural, diharapkan siswa dapat memahami nilai-nilai universal yang terkandung dalam berbagai agama, yang pada gilirannya akan memperkuat semangat toleransi dan kebersamaan. Metode yang digunakan dalam penelitian ini adalah studi kualitatif dengan pendekatan fenomenologis, yang melibatkan observasi, wawancara, dan analisis dokumen. Hasil penelitian menunjukkan bahwa penerapan pendekatan multikultural dalam PAI mampu meningkatkan sikap saling menghormati dan kerjasama antar umat beragama, sekaligus menumbuhkan rasa kebanggaan terhadap identitas agama masing-masing. Meskipun ada tantangan dalam implementasinya, seperti resistensi terhadap perubahan kurikulum dan kurangnya pemahaman tentang konsep multikultural, pendekatan ini terbukti efektif dalam menciptakan lingkungan yang lebih inklusif dan damai. Penelitian ini memberikan kontribusi terhadap pengembangan model pendidikan agama Islam yang tidak hanya berfokus pada pengajaran ajaran agama, tetapi juga pada pembentukan karakter sosial yang memperkuat kerukunan antar umat beragama. Diharapkan hasil penelitian ini dapat menjadi acuan bagi pengambil kebijakan pendidikan untuk mengimplementasikan pendekatan multikultural dalam kurikulum pendidikan agama Islam di Indonesia. Kata kunci: Pendidikan Agama Islam, Pendekatan Multikultural, Kerukunan Antarumat Beragama